2022
DOI: 10.2166/ws.2022.263
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal ARIMA model based on the gravitational search algorithm (GSA) for runoff prediction

Abstract: The prediction of river runoff is crucial for flood forecasting, agricultural irrigation and hydroelectric power generation. Coupled runoff prediction model based on the Gravitational Search Algorithm (GSA) and the Seasonal Autoregressive Integrated Moving Average (SARIMA) model is proposed to address the non-linear and seasonal features of runoff data. The GSA has a significant local optimisation capability, while the SARIMA model allows for real-time adjustment of the model using historical data and is suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, energy-related time series such as solar radiation and wind speed typically manifest seasonality and trends. To address these non-stationary characteristics, the Seasonal ARIMA (SARIMA) model has been employed, with Xianqi Z. demonstrating its high accuracy in predicting thermal energy requirements for district heating systems [36]. The SARIMA-RVFL (Random Vector Functional Link) model, designed for short-term solar photovoltaic generation predictions, and Wang H. et al 's application of the SARIMA model for monthly wind velocity forecasting have both shown improved accuracy over traditional ARIMA-based approaches [37].…”
Section: Traditional Methodsmentioning
confidence: 99%
“…However, energy-related time series such as solar radiation and wind speed typically manifest seasonality and trends. To address these non-stationary characteristics, the Seasonal ARIMA (SARIMA) model has been employed, with Xianqi Z. demonstrating its high accuracy in predicting thermal energy requirements for district heating systems [36]. The SARIMA-RVFL (Random Vector Functional Link) model, designed for short-term solar photovoltaic generation predictions, and Wang H. et al 's application of the SARIMA model for monthly wind velocity forecasting have both shown improved accuracy over traditional ARIMA-based approaches [37].…”
Section: Traditional Methodsmentioning
confidence: 99%
“…The ability of the SARIMA model to handle a larger range of data and accurately determined seasonality, as claimed by Shahriar et al ( 2021), was confirmed. The use of historical data, as in the study by Zhang et al (2022), contributed to the careful analysis of the time series and the identification of potential fluctuations that may occur when modelling future estimates. Similar findings were also confirmed in the study by Liu et al (2022), which focused on maintenance and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various intelligent optimization algorithms (Adnan et al., 2021; Yuan et al., 2018; X. Zhang et al., 2022) and signal processing techniques, such as ensemble empirical mode decomposition (EEMD) (W. C. Wang et al., 2015), complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) (Feng et al., 2022) and variational mode decomposition (VMD) (B. J. Li, Sun, Li, et al., 2022; B. J. Li, Sun, Liu, et al., 2022; Wu et al., 2023) is introduced to runoff prediction. For example, Y. Xu et al.…”
Section: Introductionmentioning
confidence: 99%